PREPARATION AND CHARACTERIZATION ION SELECTIVE ELECTRODE Cd(II) BASED ON CHITOSAN IN PVC MEMBRANE - A. Sentosa Panggabean (Universitas Gadjah Mada, 2011)
Preparation of the chitosan membrane of ion-selective electrode for determination of cadmium ion has been conducted. Chitosan is a natural polymer containing nitrogen could coordinate with Cd2+ to increase the membrane conductivity value. Chitosan is a principal material and mixed with polyvinylchloride (PVC) as matrix dissolved previously to solvent tetrahydrofuran (THF) and dioctylphenylphosphonate (DOPP) is added as plasticizer by proportion chitosan:PVC:DOPP (6:3:1). To obtain the dopant optimum concentration, membrane was dipped in Cd2+ for 7 days and its conductivity value was measured using the four-point probe method. From FT-IR spectrum the peaks of amine, acetylamide and hydroxy groups wavelength number was observed to assure that Cd2+ bound to the chitosan. The optimum concentration of Cd2+ dopant was obtained at 1.00 M with conductivity value of 549.45 ohm-1m-1 wich gave a Nernstian factor of 32.03 mV/decade with the detection limit of 2.512 x 10-5 M. The electrodes work in the pH range 3 - 7. The life time of the electrode was 8 weeks. The ions of Ni2+, Fe3+, Pb2+, Cu2+, Zn2+, Cl- and SO42- toward concentration range 10-3 M gave response did not interfere in the determine of Cd2+ ion.